2002
DOI: 10.4269/ajtmh.2002.66.71
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of tick-borne relapsing fever at the north rim of the Grand Canyon: evidence for effectiveness of preventive measures.

Abstract: Abstract. An outbreak of tick-borne relapsing fever (TBRF) originating at the North Rim of Grand Canyon National Park was investigated in 1990. To determine risk factors for the disease, almost 7,000 parties of visitors were surveyed; over half responded, representing Ͼ 10,000 people. Fifteen cases of confirmed or probable TBRF were identified in visitors and 2 in employees. All patients except one experienced symptoms after overnight stays in a group of cabins that had not been rodent-proofed after a TBRF out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…While > 7% of participants demonstrated possible prior infection with Brucella spp., these results could not be confirmed due to the potential for cross-reactivity with other bacteria, given the titer levels observed (Al Dahouk et al 2003a, 2003b. As expected, there was no serologic evidence of prior infection with B. burgdorferi, which is not endemic in either park (Bacon et al 2008), B. hermsii, which is most commonly transmitted to persons staying in poorly maintained rustic cabins (Boyer et al 1977;Trevejo et al 1998;Paul et al 2002), or Y. pestis, which is rare, with < 10 U.S. human cases reported annually (Gage and Kosoy 2005). While we cannot infer whether baseline infections occurred at the current park of employment, the background seroprevalance provides a unique cross-sectional view of this population.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…While > 7% of participants demonstrated possible prior infection with Brucella spp., these results could not be confirmed due to the potential for cross-reactivity with other bacteria, given the titer levels observed (Al Dahouk et al 2003a, 2003b. As expected, there was no serologic evidence of prior infection with B. burgdorferi, which is not endemic in either park (Bacon et al 2008), B. hermsii, which is most commonly transmitted to persons staying in poorly maintained rustic cabins (Boyer et al 1977;Trevejo et al 1998;Paul et al 2002), or Y. pestis, which is rare, with < 10 U.S. human cases reported annually (Gage and Kosoy 2005). While we cannot infer whether baseline infections occurred at the current park of employment, the background seroprevalance provides a unique cross-sectional view of this population.…”
Section: Discussionmentioning
confidence: 81%
“…Though other studies have investigated zoonotic disease risks among national parks (Boyer et al 1977;McLean et al 1989;New et al 1993;Gese et al 1997;Mills et al 1998;Paul et al 2002;Reeves 2007;Levine et al 2008;Wong et al 2009), none have addressed the breadth of pathogens evaluated here. These parks were selected due to their popularity among visitors and the likelihood of the presence of local zoonoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notable outbreaks of tick-borne relapsing fever in staff and visitors occurred in Grand Canyon National Park in 1973 (Ͼ60 conÞrmed or probable cases) and 1990 (17 conÞrmed or probable cases) (Boyer et al 1977, Paul et al 2002.…”
Section: Key Vectors and Vector-borne Pathogens Potentially Occurringmentioning
confidence: 99%
“…Six of the 16 tick-related records addressed the Rocky Mountain wood tick in Rocky Mountain National Park, including studies on the ecology of Colorado tick fever virus during an outbreak of Colorado tick fever among park visitors in the early 1970s (Carey et al 1980;Bowen et al 1981;McLean et al 1981McLean et al , 1989McLean et al , 1993a) and a recent study on the tickÕs life history . Other studies dealt with outbreaks of relapsing fever in Grand Canyon National Park (Boyer et al 1977, Paul et al 2002, the life history of the blacklegged tick in Morristown National Historical Park or along the Appalachian Trail Smith 1997, 1998;Oliver and Howard 1998), tick-host-pathogen associations on Cape Hatteras National Seashore and Assateague Island National Seashore (Oliver et al 1999), surveys for ticks and tick-borne pathogens in Yosemite National Park (Schwan et al 1993, Fleer et al 2011, and surveys for ectoparasites on vertebrates in Big South Fork National River and Recreation Area and Great Smoky Mountains National Park (Reeves et al 2007, Parker et al 2009). Other relevant studies, not recovered in the search but known to us, reported on the detection of E. chaffeensis from A. americanum ticks collected on Fire Island National Seashore (Mixson et al 2006) and public education and Lyme disease prevention in the Delaware Water Gap National Recreation Area (Hakim and Bitto 2005).…”
Section: Existing Information For Vectors and Vector-bornementioning
confidence: 99%